Pharmacogenomic Variability of Oral Baclofen Clearance and Clinical Response in Children With Cerebral Palsy. Issue 3 (1st September 2017) - McLaughlin, Matthew J.; He, Yang; Brunstrom‐Hernandez, Janice; Thio, Liu Lin; Carleton, Bruce C.; Ross, Colin J.D.; Gaedigk, Andrea; Lewandowski, Andrew; Dai, Hongying; Jusko, William J.; Leeder, J. Steven
Abstract: Background: Pharmacogenomic variability can contribute to differences in pharmacokinetics and clinical responses. Pediatric patients with cerebral palsy with genetic variations have not been studied for these potential differences. Objective: To determine the genetic sources of variation in oral baclofen clearance and clinical responses. Design: Pharmacogenomic add‐on study to determine variability in oral baclofen clearance and clinical responses. Setting: Multicenter study based in academic pediatric cerebral palsy clinics. Participants: A total of 49 patients with cerebral palsy who had participated in an oral baclofen pharmacokinetic/pharmacodynamic study. Methods or Interventions: Of 53 participants in a pharmacokinetic/pharmacodynamic trial, 49 underwent genetic analysis of 307 key genes and 4535 single‐nucleotide polymorphisms involved in drug absorption, distribution, metabolism, and excretion. Associations between genotypes and phenotypes of baclofen disposition (weight‐corrected and allometrically scaled clearance) and clinical endpoints (improvement from baseline in mean hamstring Modified Tardieu Scale scores from baseline for improvement of R1 spastic catch) were determined by univariate analysis with correction for multiple testing by false discovery rate. Main Outcome Measurements: Primary outcome measures were the genotypic and phenotypic variability of oral baclofen in allometrically scaled clearance and change in the Modified Tardieu Scale angle compared to baseline. Results: After univariate analysis of the data, the SNP of ABCC9 (rs11046232, heterozygous AT versus the reference TT genotype) was associated with a 2‐fold increase in oral baclofen clearance (mean 0.51 ± standard deviation 0.05 L/h/kg for the AT genotype versus 0.25 ± 0.07 L/h/kg for the TT genotype, adjusted P < .001). Clinical responses were associated with decreased spasticity by Modified Tardieu Scale in allelic variants with SNPs ABCC12, SLC28A1, and PPARD . Conclusions: Genetic variation in ABCC9 affecting oral baclofen clearance highlights the need for continued studies of genetic polymorphisms to better characterize variable drug response in children with cerebral palsy. Single‐nucleotide polymorphisms in ABCC12, SLC28A1, and PPARD were associated with varied responses, which warrants further investigation to determine their effect on spasticity. Level of Evidence: II